A Comparative Analysis of Smoke-Free Compliance in Aceh - Heru Syah Putra; Mirza Sahputra; Muazzinah (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Aceh Province has a smoke-free area policy. At the district level, 22 of 23 have implemented the policy. However, the effectiveness has varied significantly. One aspect of concern is compliance with establishing indoor smoke-free environments. Aims: This study conducts a comparative analysis of the success of implementing smoke-free policies in Aceh. Methods: The effectiveness is calculated based on seven indoor compliances: signage, cigarette butt, smoking, ashtray, the smell of smoke, selling, as well as cigarette advertising/promotion/ sponsorship. The data utilized are from compliance surveys conducted by the Aceh Institute in 2022 and 2023. Results: The average signage compliance is 28.45 percent with Banda Aceh City having the highest compliance at 50,8 percent. Regarding compliance with no smoking activities, the average is 88.48 percent. However, the existence of cigarette butt is relatively high, with an average of 17,69 percent with Nagan Raya having the lowest rate. This study finds three main conditions related to the effectiveness of a smoke-free policy. First, the commitment of the government to disseminate, implement, and monitor the policy. More activities conducted by the government seem to increase compliance. Second, the collaboration between government and stakeholders. Collaboration is encouraged in the policy for more effective implementation. Third, resources to implement the policy. Adequate resources improve the implementation such as the signage coverage and policy enforcement. Conclusion: The compliance level of the smoke-free policy varies in each district in Aceh. Factors that influence it are commitment, collaboration, and availability of resources.